Vice over IP. - Lubacz, J.
The anonymity of steganography might be good for privacy, but it also multiplies the threats to individuals, societies, and states. The trade-off between the benefits and threats involves many complex ethical, legal, and technological issues. We'll leave them for other thinkers and other articles. What we're trying to do is understand what kind of potential contemporary communication networks have for enabling steganography, and in effect, create new techniques so that we can figure out how to thwart them. Some readers may object to our detailed descriptions of how these methods can be harnessed. But we would counter that unless someone shows how easy all this is, researchers won't understand the urgency and be inspired to develop protective measures. Not only can VoIP steganography be implemented in telephony tools that require a laptop or PC (like Skype), it can also be used in hard phones, such as the Android VoIP-enabled mobile phones that are starting to proliferate. Steganography on a phone is more difficult, because it requires access to the device's operating system, but no one should doubt that committed individuals will have no trouble rising to the challenge.
Keywords: Android VoIP-enabled mobile phones; Contemporary communication networks; Steganography